HERMENUETIKA TERHADAP TAFSIR AL-QUR’AN - Muhammad Padlan; Muhammad Naufal Khairi; Rahmat I (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Hermeneutics is one of the efforts to understand a text, but hermeneutics also leads to the interpretation of the Qur'an which looks at the aspects of contextual, historical, authorship, and socio-psychological directions when writing. Apart from the historical principle of hermeneutics itself, there are similarities between the well-known interpretation method in the classical Islamic era and several hermeneutical models. However, when this hermeneutics is applied to the Koran, there are opinions regarding hermeneutics, starting from those who are pro-hermeneutics and there are also those who are counter-hermeneutics. Those who are pro-hermeneutics argue that the hermeneutics of the Qur'an is necessary to suit the development and progress of the times, while those who are counter-hermeneutics in the Qur'an argue that the sacredness of the Qur'an will be lost when viewed from the point of view of hermeneutics itself.